2023
DOI: 10.3390/plants12030501
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of Leaf Chlorophyll Contents (LCCs) in Litchi Based on Fractional Order Derivatives and VCPA-GA-ML Algorithms

Abstract: The accurate estimation of leaf chlorophyll content (LCC) is a significant foundation in assessing litchi photosynthetic activity and possible nutrient status. Hyperspectral remote sensing data have been widely used in agricultural quantitative monitoring research for the non-destructive assessment of LCC. Variable selection approaches are crucial for analyzing high-dimensional datasets due to the high danger of overfitting, time-intensiveness, or substantial computational requirements. In this study, the perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Mathematical transformation methods, such as spatial and frequency domains for image denoising and spectral pre-processing effects, are regarded as an effective approach to eliminate pixel spectral noise, amplify the peak and valley variations in the spectral curves, and enhance the spectral characteristics of the soil [37][38][39]. The first-order differential (FD-R) transformation can improve the signal-to-noise ratio of the response spectral bands by eliminating baseline drift and improving spectral resolution [40]; the fractionalorder differential (FOD) transformation is considered an efficient method for the peak and valley amplification of the spectra by capturing increasing subtle spectral information [41]; the Savitzky-Golay (SG) filter can remove spectral noise of hyperspectral remote sensing images in the spectral domain by smoothing spectral curves and dividing the original reflectance spectra and the envelope [42]; the continuum removal (CR) method is characterized by the highlights of the absorption and reflection features of the spectral curves, significantly diminishing the influence of terrain and illumination conditions on the spectral intensity and the absorption depth [43]. The spectral reflectance curves of hyperspectral images after pre-processing are shown in Figure 4.…”
Section: Data Processing 221 Soil Sample Selection and Chemical Analysismentioning
confidence: 99%
“…Mathematical transformation methods, such as spatial and frequency domains for image denoising and spectral pre-processing effects, are regarded as an effective approach to eliminate pixel spectral noise, amplify the peak and valley variations in the spectral curves, and enhance the spectral characteristics of the soil [37][38][39]. The first-order differential (FD-R) transformation can improve the signal-to-noise ratio of the response spectral bands by eliminating baseline drift and improving spectral resolution [40]; the fractionalorder differential (FOD) transformation is considered an efficient method for the peak and valley amplification of the spectra by capturing increasing subtle spectral information [41]; the Savitzky-Golay (SG) filter can remove spectral noise of hyperspectral remote sensing images in the spectral domain by smoothing spectral curves and dividing the original reflectance spectra and the envelope [42]; the continuum removal (CR) method is characterized by the highlights of the absorption and reflection features of the spectral curves, significantly diminishing the influence of terrain and illumination conditions on the spectral intensity and the absorption depth [43]. The spectral reflectance curves of hyperspectral images after pre-processing are shown in Figure 4.…”
Section: Data Processing 221 Soil Sample Selection and Chemical Analysismentioning
confidence: 99%
“…The reason for this approach is that spectral data have properties of redundancy and collinearity, and direct modelling with PLSR is susceptible to being disturbed by significant amounts of redundancy information [ 36 ]. GA improves model quality and stability by successfully filtering feature bands from the full spectrum [ 37 ]. The results of Sun and Zhang [ 38 ], Sun et al [ 39 ], and Zhong et al [ 17 ], who also showed that GA-PLSR outperforms PLSR in estimating heavy metal concentration using soil spectral data, are consistent with this methodology.…”
Section: Discussionmentioning
confidence: 99%
“…The variable combination cluster analysis (VCPA) algorithm optimizes the variable space by applying an exponential reduction function (EDF). Based on the model population analysis strategy, the combination of evaluation variables according to RMSECV [26]. The genetic algorithm (GA) and iterations retain information variables (IRIV) algorithm can effectively eliminate uninformative variables and optimize them globally.…”
Section: Materials and Experimentsmentioning
confidence: 99%
“…However, their time complexity is very high when faced with high‐dimensional spectral data. This experiment used the VCPA‐GA coupling algorithm and VCPA‐IRIV coupling algorithm to select the characteristic wavelengths based on the advantages of VCPA, GA, and IRIV [26, 27]. The mean number of each BMS sampling is 20 in the VCPA step.…”
Section: Materials and Experimentsmentioning
confidence: 99%